2001
DOI: 10.1021/ja003959v
|View full text |Cite
|
Sign up to set email alerts
|

Steps To Demarcate the Effects of Chromophore Aggregation and Planarization in Poly(phenyleneethynylene)s. 1. Rotationally Interrupted Conjugation in the Excited States of 1,4-Bis(phenylethynyl)benzene

Abstract: A series of photophysical measurements and semiempirical calculations were carried out with 1,4-bis(phenylethynyl)benzene in search of evidence on the effects of phenyl group rotation and chromophore aggregation of oligo- and poly(phenyleneethynylene)s. It is suggested that planarization gives rise to relatively modest shifts of ca. 20-30 nm, which preserve the vibronic structure of the monomer and retain a high emission quantum yield. In contrast, it is proposed that aggregation gives rise to larger shifts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
246
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(268 citation statements)
references
References 38 publications
19
246
2
1
Order By: Relevance
“…27 The two distinct emission spectra and extra absorption band at 365 nm reported by Levitus et al were not observed in our experiments, indicating a higher purity of the sample. 26 …”
Section: A Uv-vis and Fluorescence Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The two distinct emission spectra and extra absorption band at 365 nm reported by Levitus et al were not observed in our experiments, indicating a higher purity of the sample. 26 …”
Section: A Uv-vis and Fluorescence Studiesmentioning
confidence: 99%
“…21,24 In the ground state, the rotational barrier around the sp 2 -sp CC single bond is very low; it was determined by Greaves et al to be 220-235 cm 1 from a jet spectroscopy experiment, and this number agrees with the AM1 calculations of Levitus (0.5 kcal/mol = 180 cm 1 ). 25,26 Therefore, all rotamers ranging from planar to twisted forms are likely to co-exist at room temperature, resulting in electronic transitions at different energies. However, in the excited state, the energy difference between the planar and the twisted conformation is believed to be much larger: 15 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Different research groups have investigated the use of PAEs and hyperbranched PAEs as molecular wires, OLEDs, OSCs, OTFTs and fluorescent chemical sensors. [9][10][11][12][13][14] The interesting electronic properties exhibited by PAEs can be related to the axial symmetry of ethynylene groups, which allows to maintain the conjugation (note that between adjacent aryl groups at different relative orientations rotational barriers are as small as 1 kcal mol -1 in these cases) [15][16][17][18][19][20] across the whole molecular backbone.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The highly emissive phase of a poly(p-phenyleneethynylene) was proposed to either arise from the metastable skewed chain alignments that allowed efficient interchain interactions or result from planarization effects. [2,3] Nano-sized aggregates of a sterically crowded silole [4] and a biphenyl substituted ethylene [5] have been reported to show strong light emission, presumably due to significant ground state conformational changes accompanying the aggregate formation. These reports suggest interesting and useful application potential in areas such as electroluminescence and sensors.…”
Section: Introductionmentioning
confidence: 99%